The Effect of Addition of Liquid Organic Fertilizer (POC) to Tofu Liquid Waste on POC Kirinyuh to Increase the Number of Tillers of Rice (Oryza sativa L.) - Antje Grace Tulungen; Maria G. M. Polii; Jelie Viekson Porong; Stanley A. F. Walingkas; Beatrix Doodoh; Jeane S. M. Raintung; Stella M. Th. Tulung; Rinny Mamarimbing; Tommy Djoice Sondakh (Sam Ratulangi University, 2023)
Tofu liquid organic fertilizer (POC limbah cair tahu) and Kirinyuh liquid organic fertilizer (POC Kirinyuh) will complement each other's nutrient needs and increase rice yields. The study aims to 1) study the effect of adding POC limbah cair tahu to POC Kirinyuh to increase the number of rice plant tillers, 2) obtain the dose of POC limbah cair tahu and POC Kirinyuh in increasing the number of productive tillers of rice plants. The study used a factorial pattern Complete Randomized Design. The treatment consists of 3 treatments repeated 5 times. The treatment is: A = 50 ml POC limbah cair tahu/liter water, B = 50 ml POC Kirinyuh/ 1 liter water+50 ml POC limbah cair tahu /liter water, C = 100 ml POC Kirinyuh/ 1 liter water+50 ml POC limbah cair tahu /liter water. The variables observed were the total number of tillers and the number of productive tillers. The data were analyzed using ANOVA and if there was an effect of treatment, it was continued with the Smallest Real Difference Test (BNT) at the test level of 5%. The results showed that POC limbah cair tahu added to POC Kirinyuh increased the number of rice plant tillers. The concentration of 50 ml of POC limbah cair tahu / 1 liter of water added to 100 ml of POC Kirinyuh / 1 liter of water gives the total number of tillers and the highest number of productive tillers at 65.50 and 45.25 per pot. Keywords: number of rice plant tillers, POC tofu liquid waste, POC Kirinyuh Abstrak POC limbah cair tahu dan POC Kirinyuh akan saling melengkapi kebutuhan hara dan meningkatkan hasil tanaman padi. Penelitian bertujuan untuk 1) mempelajari pengaruh penambahan POC limbah cair tahu pada POC Kirinyuh untuk meningkatkan jumlah anakan tanaman padi, 2) Memperoleh dosis POC limbah cair tahu dan POC Kirinyuh dalam meningkatkan jumlah anakan produktif tanaman padi. Penelitian menggunakan Rancangan Acak Lengkap pola faktorial. Perlakuan terdiri dari 3 perlakuan yang diulang sebanyak 5 kali. Perlakuan tersebut adalah: A = 50 ml POC limbah cair tahu/liter air, B = 50 ml POC Kirinyuh/ 1 liter air+50 ml POC limbah cair tahu/liter air, C = 100 ml POC kirinyuh/ 1 liter air+50 ml POC limbah cair tahu/liter air. Variabel yang diamati adalah jumlah anakan total dan jumlah anakan produktif. Data dianalisis menggunakan Anova dan jika terdapat pengaruh perlakuan dilanjutkan dengan Uji Beda Nyata Terkecil (BNT) pada taraf uji 5 %. Hasil penelitian menunjukan bahwa POC limbah cair tahu yang ditambahkan pada POC Kirinyuh meningkatkan jumlah anakan tanaman padi. Konsentrasi 50 ml POC limbah cair tahu/1 liter air ditambahkan pada 100 ml POC kirinyuh/1 liter air memberikan jumlah anakan total dan jumlah anakan produktif paling banyak yaitu 65,50 dan 45,25 per pot. Kata kunci : jumlah anakan padi, POC limbah cair tahu , POC Kirinyuh